2017
DOI: 10.1021/acs.analchem.7b01567
|View full text |Cite
|
Sign up to set email alerts
|

Direct Monitoring of Exogenous γ-Hydroxybutyric Acid in Body Fluids by NMR Spectroscopy

Abstract: ABSTRACTγ-Hydroxybutyric acid (GHB) is a popular drug increasingly associated to cases of drug-facilitated sexual assault (DFSA). Currently, expanding procedures of analysis and having forensic evidence of GHB intake at a long term are mandatory. Up to now, most studies have been performed using GC-MS and LC-MS as analytical platforms, which 25 involve significant manipulation of the sample and, often, indirect measurements. In this work, procedures used in NMR-based metabolomics were applied to a GHB clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 45 publications
2
42
0
Order By: Relevance
“…While present in both treatment groups, glycolate and succinylcarnitine significantly increased in concentration due to GHB administration. Palomino‐Schätzlein et al recently also observed significant concentration increases of glycolate and succinate in urine samples after controlled GHB administration . While succinate itself was not identified in the current study, an increase in succinylcarnitine, the carnitine conjugate of succinate was observed as a follow‐up metabolite of succinate.…”
Section: Resultssupporting
confidence: 44%
See 2 more Smart Citations
“…While present in both treatment groups, glycolate and succinylcarnitine significantly increased in concentration due to GHB administration. Palomino‐Schätzlein et al recently also observed significant concentration increases of glycolate and succinate in urine samples after controlled GHB administration . While succinate itself was not identified in the current study, an increase in succinylcarnitine, the carnitine conjugate of succinate was observed as a follow‐up metabolite of succinate.…”
Section: Resultssupporting
confidence: 44%
“…This approach can also help by giving insights about the pathways implicated in the mechanism of drug action, adverse effects and variability of the drug response . A few metabolomic studies have been performed in order to further evaluate the underlying mechanisms of GHB's pharmacological action or to finally find useful biomarkers of its consumption . For example, Luca et al found up to 7‐fold higher levels of glycolate – originating form β‐oxidation of GHB – in brain and liver of mice .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 So far, few studies have focused on drugs of abuse (DOA) [14][15][16][17][18] and many of those were performed on mice and rats. Biomarker research can be used for acute or chronic drug consumption to investigate consumption behavior or to find underlying toxicological aspects of its action in humans.…”
Section: Introductionmentioning
confidence: 99%
“…16:0 (1-palmitoyl-2-hydroxy-sn-glycero-3-phosphocholine); lyso PC 18:1 (1oleoyl-2-hydroxy-sn-glycero-3-phosphocholine/lysoPC (18:1 (9Z))); lyso PE 18:arg, azelaic acid, CDA, CA, citrulline, col, con, crea, DCA, GluA, GlyA, HA, ino, ile, leu, L-pyroglutamic acid, met, MetMA, mevalonolactone, N,N-dimethylglycine, nicotinic acid, p-aminobenzoic acid, phe, pro, raffinose, riboflavin, taurine, TA, trp, and uracil (concentration 10 μg/mL each) was measured in the beginning, middle, and at the end of each measurement method and checked for reproducibility of the data by retention time (RT) shifts and peak area comparison using MultiQuant V 2.1 (Sciex, Concord, Ontario, Canada).…”
mentioning
confidence: 99%